2010
DOI: 10.1021/jp105973e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation of the Pressure-Induced Crystallographic Phase Transition of p-Terphenyl

Abstract: The pressure- and temperature-induced polymorphic crystal phase transitions of p-terphenyl (PTP) have been modeled using a modified PCFF interaction force field. Modifications of the interaction potential were necessary to simultaneously model both the temperature-induced phase transition at ambient pressure and the pressure-induced phase transition at low temperature. Although the high-temperature and high-pressure phases are both characterized by flattening of the PTP molecule, the mechanisms of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…The structural analysis of 40 HB-PAHs under hydrostatic pressure is based on methods previously used by us to investigate the property−structure relationships of crystalline PAHs and other small OMCs under both ambient and high-pressure conditions. 1,6,10,15,19,22 Here, as well as in the previous investigations, PBE + vdW provides excellent agreement between the calculated and experimental structural descriptors (e.g., lattice parameters, internal molecular geometries, intermolecular close contacts, and density). The agreement between the calculated and experimental unit cell parameters and densities is within ∼2% for structures at nearly all pressures.…”
Section: Resultssupporting
confidence: 84%
“…The structural analysis of 40 HB-PAHs under hydrostatic pressure is based on methods previously used by us to investigate the property−structure relationships of crystalline PAHs and other small OMCs under both ambient and high-pressure conditions. 1,6,10,15,19,22 Here, as well as in the previous investigations, PBE + vdW provides excellent agreement between the calculated and experimental structural descriptors (e.g., lattice parameters, internal molecular geometries, intermolecular close contacts, and density). The agreement between the calculated and experimental unit cell parameters and densities is within ∼2% for structures at nearly all pressures.…”
Section: Resultssupporting
confidence: 84%
“…The shortest cell axis then transitions into a new motif bracket while q remains uncharacteristic of that motif. 3,6,9,10 Table 3 lists several high pressure and low temperature PAH structures accompanied by their intermolecular interactions, motif assignment and q. It was observed that naphthalene undergoes no observable motif variation upon pressurization.…”
Section: Analysis Of High-pressure Structuresmentioning
confidence: 99%
“…5 It has been shown that when crystalline PAHs are placed under pressure three mechanisms of energy minimization exist: (1) any twists in the molecule become flattened, (2) all unit cell axes become compressed and (3) the interplanar angle (q) and molecular set angle (c) adjust to allow for more efficient packing. [6][7][8] Upon pressurization, the motif assignment of a PAH can change as its crystal defining axis (usually b) and q values adjust. In studies of several PAHs under pressure, 3,9,10 the shortening of b moves the PAH into a new motif bracket, but the pressurized crystal does not exhibit the motif's typical q distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallinity in polymeric systems has enormous significance in chemistry, biology, and materials science. [1][2][3] It profoundly affects the physical properties and thermal stabilities 4-6 of polymeric materials, and is influenced by factors such as stereoregularity, 7 pi-pi stacking, 8 mainchain rigidity, 9 end-group dependence, 10 and hydrogen bonding. 11 An illustrative example of crystallinity's influence on polymer properties resides in stereoregular polyolefins; where high crystallinity improves solvent resistance, high-temperature performance, and degradation time.…”
Section: Introductionmentioning
confidence: 99%